The American Society for Clinical Pathology's 2017 Wage Survey of Medical Laboratories in the United States. Issue 1 (1st October 2018) - Garcia, Edna; Kundu, Iman; Fong, Karen
Abstract: Objectives: To inform the pathology and laboratory field of the most recent national wage data. Historically, the results of this biennial survey have served as a basis for additional research on laboratory recruitment, retention, education, marketing, certification, and advocacy. Methods: The 2017 Wage Survey was conducted through collaboration between the American Society for Clinical Pathology's (ASCP's) Institute of Science, Technology, and Policy in Washington, DC, and the ASCP Board of Certification in Chicago, IL. Results: Compared with 2015, results show an overall increase in salaries for most of the laboratory occupations surveyed except histotechnologists and pathologists' assistants. Geographically, laboratory professionals from urban areas earn more than their rural counterparts. Conclusions: Survey results encourage laboratory professionals to be actively engaged in advocating for the profession in the workforce and educational training programs. Awareness of the career opportunities and value of the profession is needed to strengthen the future of the field.